A Twelve-Beam Steering Low Profile Patch Antenna with Shorting Vias for Vehicular Applications - Amit Mehta (IEEE Transactions on Antennas and Propagation, 2017)
A low-profile twelve-beam printed patch antenna is presented for pattern reconfigurable applications. The patch is fed at the four sides using coaxial feeds. Diagonal lines of vias are inserted on the patch surface to restrict currents to the edges. Whilst majority of patch antennas have only axial beam pattern, the proposed antenna produces twelve different beams. When one of its four feeds on the sides is excited and the remaining feeds are open circuited, the antenna generates a linearly polarized tilted beam (6.1 dBi, θmax = 30°). This beam is directed away from feeding patch corner. Therefore, the antenna can steer its tilted beam in four different space quadrants in front of the antenna by exciting one feed at a time. The antenna is also capable of generating eight other beams using multiple feed excitations. They are four additional titled beams (6.1 dBi, θmax=30°), two tilted-twin beam (5.8 dBi, θmax=±36°), one semi-doughnut beam (5.8 dBi) and one axial beam (8.2 dBi). The antenna is designed to operate at test frequency of 2.4 GHz and has a height = 1.5 mm (λ0/83). The impedance matching to 50 Ω is achieved using right angle slots etched on the patch antenna.